INTEGRATION OF INDIAN PRINCELY STATES AFTER INDEPENDENCE: A CRITICAL ASSESSMENT OF THE ROLE OF SARDAR VALLABHBHAI PATEL - Kumar, Sandeep (International Journal of Research -GRANTHAALAYAH, 2026)
The present paper analyzes the complex process of merging over 560 autonomous princely states into the Indian Union after India’s independence in 1947. The primary focus of the research is to evaluate the strategic foresight, diplomatic acumen, and strong will of the then Home Minister, Sardar Vallabhbhai Patel. After the end of British rule’s paramountcy, India faced a serious threat of Balkanization (fragmentation). This paper examines how Patel, in collaboration with V.P. Menon, ensured the integration of Junagadh, Hyderabad, and other challenging princely states by adopting a policy of "coercion, bribery, punishment, and discrimination." The study not only highlights his successes but also critically evaluates the difficult decisions he made—such as the promise of the Privy Purse and the use of military force in some instances. In conclusion, this paper argues that the geographical and political unity of modern India would not have been possible without Sardar Patel, and calling him the ’Bismarck of India’ is a fitting tribute to his historical contribution.